Spatial Mismatching of Residents’ Visible Greening with Green Coverage under the Influence of Urban Morphology - Danqi Guo; Sophia Shuang Chen (Ecosystem Health and Sustainability)
Compared with urban streets and parks, the greening of residential areas is characterized by diverse tree species and landscapes and is closely related to the daily life of residents. This study comprehensively assessed the green view index (GVI) in residential areas through analyzing 4,607 panoramic photographs collected in 17 residential quarters in Nanjing in different seasons. The spatial matching between GVI and green coverage was quantitatively characterized alongside their spatial distribution, and the effect of urban morphological factors on GVI was investigated to propose a planning strategy for greening promotion. The results show the following: (a) The GVI range is 0.0% to 81.0%, with an average value of 29%. Regardless of seasons, the average fractional vegetation cover (FVC) exceeds the average GVI, indicating substantial potential for green space improvement and requirement of interventions. (b) Around 50% of measured grids have a mismatch between GVI and FVC, and the matching degree is in the following descending order: mid-rise > high-rise > low-rise residential quarters. The mismatch area with high FVC but low GVI displays marginal distribution characteristics, which belongs to the space of GVI potential enhancement. (c) Morphological factors such as road width and intersection numbers significantly influence GVI, while building density and height have no statistical impact. It is highly suggested to increase GVI in high-density residential areas to foster healthier and more inclusive urban environments. The results of this study contribute to a deep understanding of the matching relationship between GVI and green coverage and have reference significance for similar studies.